The Feasibility of Guided Inquiry-Based Digital Flipbook Learning Media: Physics Module in Sensing Systems (Department of Physics, Faculty of Mathematics and Natural Sciences, 2023)
Various technology-based learning media have now been widely developed but sometimes in their use some of them are still not maximized properly. The current modernization of education refers to the digitalization of current learning making digital media not only used as a media of communication but also as a medium of learning so that students can carry out learning activities online or blended learning. Online learning or blended learning requires students to be skilled at using digital devices. Besides that, now we are also in the digital era which demands that all aspects of life, including learning activities, participate in training students to use digital systems, one of which is as a learning media. The way to train students' skills in using digital devices is to introduce and familiarize students with using digital media when the learning process starts from the simplest, such as flipbook e-modules. This study aims to determine the feasibility of the digital physics flipbook module in guided inquiry-based sensing. The research method used is research and development research with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The methods used to collect data are observation, interviews, and questionnaires. The instrument used to collect data is a questionnaire. The feasibility test was carried out by distributing validation sheets to junior high school science teachers, high school physics teachers, and science education students. The research results obtained are the digital physics flipbook module in the sensing system has been feasible to use with a percentage of 80% and is in the very good category. Thus the guided inquiry-based e-module flipbook on physics material in this sensing system has been worthy of being used as teaching materials and learning media for students.